2010
DOI: 10.1093/nar/gkq804
|View full text |Cite
|
Sign up to set email alerts
|

RNA G-Quadruplexes in the model plant species Arabidopsis thaliana: prevalence and possible functional roles

Abstract: Tandem stretches of guanines can associate in hydrogen-bonded arrays to form G-quadruplexes, which are stabilized by K+ ions. Using computational methods, we searched for G-Quadruplex Sequence (GQS) patterns in the model plant species Arabidopsis thaliana. We found ∼1200 GQS with a G3 repeat sequence motif, most of which are located in the intergenic region. Using a Markov modeled genome, we determined that GQS are significantly underrepresented in the genome. Additionally, we found ∼43 000 GQS with a G2 repea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
88
2

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(102 citation statements)
references
References 101 publications
(128 reference statements)
7
88
2
Order By: Relevance
“…The human genome has a PQS density of 0.13/Kb [10] and the highest PQS density reported in literature for any organism is 0.19/Kb, for the mouse genome [25]. Interestingly, in our study we found PQS densities as high as 1.037/Kb (Fig.…”
Section: Resultssupporting
confidence: 61%
“…The human genome has a PQS density of 0.13/Kb [10] and the highest PQS density reported in literature for any organism is 0.19/Kb, for the mouse genome [25]. Interestingly, in our study we found PQS densities as high as 1.037/Kb (Fig.…”
Section: Resultssupporting
confidence: 61%
“…1A, top left). The genomes of humans and many other eukaryotes are replete with putative G4-forming sequences, and pronounced, conserved patterns have been observed in their distribution, suggesting that Gquadruplex structures form at least transiently in cells and perform conserved functions (2)(3)(4)(5)(6). Supporting this hypothesis, G4s have been detected in cells for both DNA and RNA (7)(8)(9)(10)(11).…”
Section: ___________________________________mentioning
confidence: 91%
“…The single stranded nature of RNA is also thought to increase the likelihood of these structures forming in vivo. Increasing the number of G-tetrads [47,49,50] and shortening loop length [45,48] leads to the formation of more stable structures with a lower dependence on monovalent cations such as K + [47]. Unsurprisingly, the predicted prevalence of PQS within 5 -UTRs depends largely on the sequence parameters imposed on the computational search.…”
Section: A Role Of Eif4a Activity In Unwinding G-quadruplex Structurementioning
confidence: 99%
“…Unsurprisingly, if these parameters are relaxed to allow PQS with only two stacks of G-tetrads and/or longer loop lengths, many more PQS would be identified. However, although G-quadruplexes with just two stacks of G-tetrads are able to form under the correct conditions [24,49,50], the structural preferences of CGG repeats remains under debate. Malgowska et al [51] investigated G-quadruplex formation for CGG, AGG and UGG trinucleotide repeats in various conditions using multiple techniques.…”
Section: A Role Of Eif4a Activity In Unwinding G-quadruplex Structurementioning
confidence: 99%
See 1 more Smart Citation